Proceedings of the 17th International Symposium on Computer and Information Sciences : ISCIS XVII, October 28-30, 2002, Orlando, Florida, USA /: ISCIS XVII, October 28-30, 2002, Orlando, Florida, USA. (2022) - Unknown
No abstract available